Human urine-derived renal epithelial cells provide insights into kidney-specific alternate splicing variants. (December 2018) - Molinari, Elisa; Decker, Eva; Mabillard, Holly; Tellez, James; Srivastava, Shalabh; Raman, Shreya; Wood, Katrina; Kempf, Caroline; Alkanderi, Sumaya; Ramsbottom, Simon; Miles, Colin G.; Johnson, Colin A.; et al.
Abstract The majority of multi-exon genes undergo alternative splicing to produce different mRNA transcripts and this may occur in a tissue-specific manner. Assessment of mRNA transcripts isolated from blood samples may sometimes be unhelpful in determining the affect on function of putative splice-site variants affecting kidney-specific mRNA transcripts. Here we present data demonstrating the power of using human urine-derived renal epithelial cells (hUREC) as a source of kidney RNA. We report clinical and molecular genetic data from three affected cases from two families all with end-stage renal disease by 15 years of age. In both families, heterozygous variants which are predicted to effect function inNPHP3 were found on one allele, in combination with a synonymous SNV (c.2154C>T; p.Phe718=), 18 base pairs from the exon–intron boundary within exon 15 ofNPHP3 . The only mRNA transcript amplified from wild-type whole blood showed complete splicing out of exon 15. Urine samples obtained from control subjects and the father of family 2, who carried the synonymous SNV variant, were therefore used to culture hUREC and allowed us to obtain kidney-specific mRNA. Control kidney mRNA showed retention of exon 15, while the mRNA from the patient's father confirmed evidence of a heterozygous alternate splicing of exon 15 ofNPHP3 . Analysis of RNA derived from hUREC allows for a comparison of kidney-specific and whole-blood RNA transcripts and for assessment of the effect on function of putative splice variants leading to end-stage kidney disease.